Tourism eco-efficiency: Progress and prospect - Rahawarin, Muhammad Fikruzzaman; Mizuno, Kosuke; Karuniasa, Mahawan (Turyzm/Tourism, 2025)
This study aims to analyse relevant literature on tourism eco-efficiency which has arrived since this terminology was proposed almost two decades ago. This study was conducted using bibliometric analysis based on literature findings from the Scopus database, filtered by the ROSES framework, which resulted in a collection of 99 articles between 2005 and 2023, further analysed using the Biblioshiny package in R. We conducted five analyses, including general and source-based – to explore the most relevant and impactful journals, author-based – to highlight the most frequently cited productive researchers, and country-based – to identify those with consistent research networks and an abundant output on related topics. Additionally, there was keyword-based – emphasizing the evolution of tourism eco-efficiency discourse over time. This keyword-based analysis is further divided into factorial – clustered keywords; and thematic – grouping keywords into quadrants offering retrospective insight and identifying unexplored topics for future research. The findings of this study propose valuable insights into the topic of tourism eco-efficiency and propose further research directions, including those on spatial analysis, tourism spillover effects, integration with environmental regulations and interdisciplinary collaborations.